Characteristics of emerging new autoimmune diseases after COVID-19 vaccination: A sub-study by the COVAD group - Shumnalieva, Russka; Ravichandran, Naveen; Hannah, Jennifer; Javaid, Mahnoor; Darooka, Naitica; Roy, Debaditya; Gonzalez, Daniel E.; Velikova, Tsvetelina; Milchert, Marcin; Kuwana, Masataka; Joshi, Mrudula; Gracia-Ramos, Abraham Edgar; et al. (International Journal of Rheumatic Diseases, 2024)
Background: Despite the overall safety and efficacy of COVID-19 vaccinations, rare cases of systemic autoimmune diseases (SAIDs) have been reported post-vaccination. This study used a global survey to analyze SAIDs in susceptible individuals' post-vaccination. Methods: A cross-sectional study was conducted among participants with self-reported new-onset SAIDs using the COVID-19 Vaccination in Autoimmune Diseases (COVAD) 2 study dataset—a validated, patient-reported e-survey—to analyze the long-term safety of COVID-19 vaccines. Baseline characteristics of patients with new-onset SAIDs and vaccinated healthy controls (HCs) were compared after propensity score matching based on age and sex in a 1:4 ratio. Results: Of 16 750 individuals, 74 (median age 52 years, 79.9% females, and 76.7% Caucasians) had new-onset SAID post-vaccination, mainly idiopathic inflammatory myopathies (IIMs) (n = 23, 31.51%), arthritis (n = 15; 20.53%), and polymyalgia rheumatica (PMR) (n = 12, 16.40%). Higher odds of new-onset SAIDs were noted among Caucasians (OR = 5.3; 95% CI = 2.9–9.7; p <.001) and Moderna vaccine recipients (OR = 2.7; 95% CI = 1.3–5.3; p =.004). New-onset SAIDs were associated with AID multimorbidity (OR = 1.4; 95% CI = 1.1–1.7; p <.001), mental health disorders (OR = 1.6; 95% CI = 1.3–1.9; p <.001), and mixed race (OR = 2.2; 95% CI = 1.2–4.2; p =.010), where those aged >60 years (OR = 0.6; 95% CI = 0.4–0.8; p =.007) and from high/medium human development index (HDI) countries (compared to very high HDI) reported fewer events than HCs. Conclusion: This study reports a low occurrence of new-onset SAIDs following COVID-19 vaccination, primarily IIMs, PMR, and inflammatory arthritis. Identified risk factors included pre-existing AID multimorbidity, mental health diseases, and mixed race. Revaccination was well tolerated by most patients; therefore, we recommend continuing COVID-19 vaccination in the general population. However, long-term studies are needed to understand the autoimmune phenomena arising post-vaccination.
CRIS-Team Scopus Importer:2024-05-24
Keywords: autoimmune diseases; COVID-19; idiopathic inflammatory myopathies; SAIDs; vaccination